1977
DOI: 10.1021/bi00629a028
|View full text |Cite
|
Sign up to set email alerts
|

Studies on native ribosomal subunits from rat liver. Purification and characterization of a ribosome dissociation factor

Abstract: A population of free, native ribosomal 40S subunits, that do not react with 60S subunits to form 80S ribosomes, has been identified in the postmicrosomal fraction of rat liver homogenates. A protein (IF-3) has been purified from high salt (0.88 M KCI) extracts of native 40S subunits by gradient centrifugation and by ammonium sulfate fractionation; it prevents the reassociation of subunits and to a limited extent dissociates ribosomes to subunits. The activity is measured by ultracentrifugation of the reaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
44
0

Year Published

1979
1979
2008
2008

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(44 citation statements)
references
References 45 publications
0
44
0
Order By: Relevance
“…Two protein factors, eukaryotic translation initiation factor 3 (eIF3) and eIF6, have been implicated in this process (1)(2)(3)(4)(5). It has been reported that eIF3, a multisubunit protein complex of M r Ͼ 500,000, binds to the 40S ribosomal subunit and prevents its association with the 60S ribosomal subunit to form 80S ribosomes (8)(9)(10)(11). In contrast to eIF3, eIF6, a monomeric protein of about 25 kDa, has been shown to bind to the 60S ribosomal subunit and prevents its association with the 40S ribosomal subunit (12)(13)(14)(15).…”
mentioning
confidence: 99%
“…Two protein factors, eukaryotic translation initiation factor 3 (eIF3) and eIF6, have been implicated in this process (1)(2)(3)(4)(5). It has been reported that eIF3, a multisubunit protein complex of M r Ͼ 500,000, binds to the 40S ribosomal subunit and prevents its association with the 60S ribosomal subunit to form 80S ribosomes (8)(9)(10)(11). In contrast to eIF3, eIF6, a monomeric protein of about 25 kDa, has been shown to bind to the 60S ribosomal subunit and prevents its association with the 40S ribosomal subunit (12)(13)(14)(15).…”
mentioning
confidence: 99%
“…Bergmann, J. Gordon and D. Baltimore). It is known that the majority of native 40S subunits contain eIF-3 (33,34), and the same factor binds specifically to 40S subunits in vitro (29,30). Consequently, it is tempting to suggest that in vivo a pre-initiation complex between mRNA and the 24,000 dalton capbinding polypeptide is directed to eIF-3-containing 40S ribosomal subunits at least partly by an interaction between the eIF-3 and the cap binding protein.…”
mentioning
confidence: 99%
“…elF-3 is a large complex of ten different subunits ranging from 110 kDa to 34 kDa (Fig. 1, lane C) [38][39][40][41]. The results of the crosslinking experiment (lane D), shows that only three of them are in direct contact with the SFV mRNA molecule.…”
Section: Resultsmentioning
confidence: 96%